Smart Water Management for Irrigation Purposes: The SWSOIP Pproject - Papoutsa, Christiana; Theocharidis, Christos; Prodromou, Maria; Papadavid, George; Sykas, Dimitris; Michaelides, Silas; Christoforou, Michalakis; Kountios, Georgios; Kounoudes, Anastasis; Milis, Marios; Hadjimitsis, Diofantos G. (My University, 2020)
It seems that the future scenarios for water resources management are characterized by increasing demand and by the short-term unsustainability of many reservoirs in the Mediterranean basin. To address these scenarios, improved management of water resources was needed for water economy, and water recycling policies. Furthermore, agriculture characterized as the largest water user worldwide and the monitoring of the agriculture via remote sensing techniques is an enormous subject where it used for special scientific applications such as irrigation, precision farming, yield prediction, estimation of evapotranspiration etc. The main objective of this paper is to present the current situation of water resources in the Mediterranean region and present the methodology and main objectives of the SWSOIP project which aims to develop a smart watering system for the irrigation process based on the estimation of evapotranspiration using both in-situ data (spectroradiometric, LAI, CH and meteorological) and Sentinel satellite data.
Keywords: Water management; Agriculture; Remote sensing; Smart watering system